Portuguese Presidency of the Council of the European Union - de Farmacoterapia, Revista Portuguesa (2021)
The fourth Portuguese Presidency of the Council of the European Union will have the motto “Time to deliver: for a fair, green and digital recovery” and will take place from January 1st to June 30th, 2021. This document seeks to describe a brief summary of main objectives and priorities defined for this period, with particular emphasis in the area of health.The program of the Portuguese Presidency of the Council of the European Union can be consulted at: https://www.2021portugal.eu/media/rohpisqf/portuguese-presidency-en.pdf